2006
DOI: 10.1097/01.ajp.0000210929.43192.5d
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pain in Reduced Quality of Life and Depressive Symptomology in Children With Spina Bifida

Abstract: The unmanaged pain in children with spina bifida can have a substantial negative impact on quality of life. Better treatment and surveillance of pain and depression symptoms may significantly improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 45 publications
(45 reference statements)
3
48
0
3
Order By: Relevance
“…Parents of the 50 subjects were interviewed in person during the MM clinic using two HRQOL outcome tools: the PedsQL TM Version 4.0 [7,[24][25][26][27] parent version for young children (ages 5-7), children (ages [8][9][10][11][12], and the teen report (ages [13][14][15][16][17][18]; and the PODCI Version 2.0 [10] parent form for children (ages 2-18). Because of concerns about time and length of the instrument, 22% of the parents declined to complete the PODCI questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Parents of the 50 subjects were interviewed in person during the MM clinic using two HRQOL outcome tools: the PedsQL TM Version 4.0 [7,[24][25][26][27] parent version for young children (ages 5-7), children (ages [8][9][10][11][12], and the teen report (ages [13][14][15][16][17][18]; and the PODCI Version 2.0 [10] parent form for children (ages 2-18). Because of concerns about time and length of the instrument, 22% of the parents declined to complete the PODCI questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies [4,6,[15][16][17][18][19][20][21][22] have looked at quality of life for persons with MM using a variety of outcome tools for parents and for youth. Several studies have suggested an inverse relationship [18,20,22] between health-related quality of life (HRQOL) and the lesion level, whereas others report no [4,6,17] or only a partial [15] relationship between the two.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations